Future perspectives for surgical research in Germany - Diener, Markus K.; Menger, Michael D.; Jähne, Joachim; Saeger, Hans-Detlev; Klar, Ernst (Langenbeck's archives of surgery, 2014)
During the last two decades, the complexity of surgical patient care has increased dramatically. Nonetheless, there is substantial need to improve the quality of surgical research in Germany.